(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2019)
Multi-material additive manufacturing brings new possibilities for the production of flexible and functional medical models for training and planning of surgical interventions. Based on the large amount of available material combinations, materials are poorly characterized and process related variations in the material properties are not completely understood. Aim of this study was a dimensional and mechanical characterization of selected pure materials and material-combinations under investigation of build orientation effects.